2021
DOI: 10.3389/fmed.2021.680302
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Clinical Trials Registration for Lupus Nephritis Therapy on ClinicalTrials.gov

Abstract: Objective: Clinical trials are the most effective method for evaluating therapeutic strategies. The purpose of this study was to comprehensively assess the characteristics of trials on lupus nephritis (LN) and provide a reference for LN treatment and research.Methods: Registered therapeutic trials on drug interventions for LN were obtained from ClinicalTrials.gov up to December 3, 2020. The general characteristics, methodological characteristics, detailed characteristics, investigated drugs, eligibility criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Joseph S Ross et al reviewed the clinical trials funded by NIH in ClinicalTrials.gov, their results showed that within 30 months of the trials' completion, only 294 (46%) were published in the peer-reviewed journals [23]. Similarly, two studies indicated that around 70% of the studies had no web links for the publications of results on ClinicalTrials.gov [25,26]. Except for the experiment being incomplete, there might exist a number of factors resulting in these low publication rates, including that journals tended to report only "positive" research in terms of publication bias or the researchers did not release their findings [27].…”
Section: Discussionmentioning
confidence: 99%
“…Joseph S Ross et al reviewed the clinical trials funded by NIH in ClinicalTrials.gov, their results showed that within 30 months of the trials' completion, only 294 (46%) were published in the peer-reviewed journals [23]. Similarly, two studies indicated that around 70% of the studies had no web links for the publications of results on ClinicalTrials.gov [25,26]. Except for the experiment being incomplete, there might exist a number of factors resulting in these low publication rates, including that journals tended to report only "positive" research in terms of publication bias or the researchers did not release their findings [27].…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive study of clinical trials in LN registered with ClinicalTrials.gov lists as many as 126 RCTs initiated between 1998 and 2020, including those for 27 types of biological agents. 5 Among these, anti-inflammatory agents act acutely by limiting immunologic damage, making them useful as induction agents. Therapies that target autoimmunity work toward attenuating disease activity and thus prevent accruing damage from repeated flares.…”
Section: Novel Therapeutic Targets For Lupus Nephritismentioning
confidence: 99%
“…Таким образом, проблема фармакотерапии СКВ (табл. 2) продолжает оставаться одной из центральных в современной ревматологии и для ее решения необходима интенсификация клинических и научных исследований [205].…”
Section: проблемы системной красной волчанки в XXI векеunclassified